Fiction's in the Know: Reassessing Epistemologies of Cognitive Science and (Un)Consciousness (KULT_online, 2013)
In Fictions of Cognition, Stephan Freißmann focuses on the circulation of ideas between scientific and literary writing. To sketch out what he argues to be a dialogic relationship between what he calls 'fictions of cognition' and cognitive science, the study focuses on the types of knowledge of cognition that can be formed on the basis of fiction, and the representation of (un)consciousness and cognitive science in fiction. After asserting the epistemic power of fiction and significantly expanding the spectrum of elements of narrative able to represent consciousness, six contemporary English and American novels, 'fictions of cognition', are analyzed in pairs according to dominant theme and their stance toward consciousness and/or cognitive science. The book convincingly relativizes the authority of science by emphasizing the cultural dynamics inherent in the negotiation process of knowledge formation. It is well-argued, intelligible, and an overall thought-provoking, relevant contribution to cognitive literary and cultural studies.